Honeybee Royal Jelly and Nobiletin Stimulate CRE-Mediated Transcription in ERK-Independent and -Dependent Fashions, Respectively, in PC12D Cells - Hironori Fujiwara; Ako Kogure; Masahiro Sakamoto; Tohru Yamakuni; Yoshihiro Mimaki; Kiyoshi Murata; Nobuyuki Hitomi; Kikuji Yamaguchi; Yasushi Ohizumi (Elsevier, 2011)
Abstract.: To prove the pharmacological actions of honeybee royal jelly (RJ) on the nervous system, we examined the effects of RJ on CRE-mediated transcription. RJ increased CRE-mediated transcription in PC12D cells. Moreover, CRE-mediated transcriptional activity by RJ was enhanced by nobiletin. U0126, a MEK inhibitor, inhibited CRE-mediated transcription by combining RJ plus nobiletin without affecting transcription by RJ alone. These results suggest that RJ stimulates CRE-mediated transcription via an ERK-independent cascade, whereas the increasing CRE-mediated transcriptional effect by nobiletin is dependent on ERK phosphorylation. Combining RJ plus nobiletin may activate effectively neuronal functions via enhancement of CRE-mediated transcription. Keywords:: honeybee royal jelly, CRE-mediated transcription, Alzheimer's disease